2009
DOI: 10.1074/jbc.m109.004010
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of Endogenous Nicotinamide Riboside Is Essential for Calorie Restriction-mediated Life Span Extension in Saccharomyces cerevisiae

Abstract: NAD؉ (nicotinamide adenine dinucleotide) is an essential cofactor involved in various biological processes including calorie restriction-mediated life span extension. Administration of nicotinamide riboside (NmR) has been shown to ameliorate deficiencies related to aberrant NAD ؉ metabolism in both yeast and mammalian cells. However, the biological role of endogenous NmR remains unclear. Here we demonstrate that salvaging endogenous NmR is an integral part of NAD ؉ metabolism. A balanced NmR salvage cycle is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
117
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(125 citation statements)
references
References 49 publications
8
117
0
Order By: Relevance
“…Relative NR levels were determined by a liquid-based cross-feeding bioassay (12). To prepare cell extracts for intracellular NR determination, ϳ1.5 ϫ 10 9 (ϳ150 A 600 unit cells) of cells (donors of interest) grown to late logphase (ϳ12 h growth from an A 600 of 0.1) were lysed by bead beating in 800 l of ice-cold 50 mM ammonium acetate solution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Relative NR levels were determined by a liquid-based cross-feeding bioassay (12). To prepare cell extracts for intracellular NR determination, ϳ1.5 ϫ 10 9 (ϳ150 A 600 unit cells) of cells (donors of interest) grown to late logphase (ϳ12 h growth from an A 600 of 0.1) were lysed by bead beating in 800 l of ice-cold 50 mM ammonium acetate solution.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, NR has been shown to be an efficient NAD ϩ precursor that contributes to the NAD ϩ pool and supports NAD ϩ -dependent reactions (9,10). Intact NR salvaging pathway is essential for maintaining NAD ϩ homeostasis and life span (12,13). Because yeast cells constantly release and reassimilate NR, it has been suggested that this NR pool might confer metabolic flexibility for prompt adjustment of cellular NAD ϩ levels (12,13).…”
Section: Pyridine Nucleotides Nadmentioning
confidence: 99%
See 1 more Smart Citation
“…However, molecular mechanisms that underlie these beneficial effects remain unclear. (19). To further understand the regulation of NAD + homeostasis, we developed a NR-specific reporter-based bioassay to screen for mutants with altered NR release.…”
mentioning
confidence: 99%
“…To further understand the regulation of NAD + homeostasis, we developed a NR-specific reporter-based bioassay to screen for mutants with altered NR release. This screen system was based on our observations that yeast cells release and transport NR back into the cell (19), a phenomenon that is also conserved in human cells (20). Our studies have identified novel NAD + homeostasis factors including the phosphate responsive signaling (PHO) pathway (17), the SPS amino acid sensing pathway (21), a conserved vacuolar NR transporter Fun26 (1,17) and several NAD + metabolic enzymes (22).…”
mentioning
confidence: 99%